DESIGN OF DORMITORY STRUCTURE WITH STEEL SPECIAL MOMENT FRAMES - Amhudo, Rasyiid Lathiif; Utomo, Dwi Prasetyo (Journal of Civil Engineering and Infrastructure Technology, 2024)
Colomadu District is one of the districts located in Karanganyar Regency, Central Java Province. It is projected that the economy in this area will grow through business sectors such as goods and services, tourism, and industry, thus the construction of a Dormitory Building is planned in the area. Considering its proximity to Yogyakarta Province, which frequently experiences earthquakes, earthquake-resistant buildings are necessary to reduce the risk of casualties and material losses. Therefore, the design of this building utilizes a Special Moment Resisting Frame (SRPMK) system. The building with SRPMK is designed with the concept of SCWC (Strong Column and Weak Beam), where the column elements are stronger than the beam elements. This design aims to create a structural system that can withstand seismic forces, in accordance with SNI 2847:2019 requirements. Seismic force loading is analyzed using the response spectrum method, and the structural calculations are performed using ETABS V9.7.4 software. From the planning results, the dimensions obtained include a Bondek floor slab thickness of 130 mm, beam dimensions B1A 150x400 mm, B2A 200x400 mm, B2B 200x400 mm, B2C 200x400 mm, B2D 200x400 mm, B2E 200x400 mm, B3A 200x500 mm, B3B 200x500 mm, B4A 300x150 mm, B5A 300x150 mm, BS 150x300 mm, and column dimensions KP 150x150 mm, K1A 200x300 mm, K2A 400x550 mm, K3A 450x650 mm, and K4 350x500 mm.